Exploring CNS Effects of American Traditional Medicines using Zebrafish Models - de Abreu, Murilo S.; Costa, Fabiano; Giacomini, Ana C.V.V.; Demin, Konstantin A.; Petersen, Elena V.; Rosemberg, Denis B.; Kalueff, Allan V. (Current Neuropharmacology, 2022)
Although American traditional medicine (ATM) has been practiced for millennia, its complex multi-target mechanisms of therapeutic action remain poorly understood. Animal models are widely used to elucidate the therapeutic effects of various ATMs, including their modulation of brain and behavior. Complementing rodent models, the zebrafish (Danio rerio) is a promising novel organism in translational neuroscience and neuropharmacology research. Here, we emphasize the growing value of zebrafish for testing neurotropic effects of ATMs and outline future directions of research in this field. We also demonstrate the developing utility of zebrafish as complementary models for probing CNS mechanisms of ATM action and their potential to treat brain disorders.
Keywords: animal models